Entrepreneurial mindfulness and organizational resilience of Chinese SMEs during the COVID-19 pandemic: The role of entrepreneurial resilience - Liu, Xuepeng; Wu, Xiaohang; Wang, Qing; Zhou, Zhenzhen (Frontiers in Psychology, 2022)
Organizational resilience is vital to the survival and thriving of enterprises, especially during the COVID-19 pandemic. Although there has been an increasing interest in organizational resilience, the effects from the entrepreneur perspective receive scant attention. Based on upper echelons theory (UET) and personality psychology, we propose a model in which entrepreneurial mindfulness and entrepreneurial resilience could influence organizational resilience of SMEs. We empirically analyzed a sample of 180 entrepreneurs managing small- and medium-sized enterprises (SMEs) in China during the COVID-19 pandemic, using SmartPLS software. The research findings indicated that entrepreneurial mindfulness is positively associated with organizational resilience and such relationship is partially mediated by entrepreneurial resilience. These findings convey important theoretical implications in this field of research as well as practical implications for SMEs in China or other countries with similar nature.